Job changes, hours changes and the path of labour supply adjustment - Richard Blundell; Mike Brewer; Marco Francesconi (Institute for Fiscal Studies (IFS), 2005)
This paper uses the first twelve waves of the British Household Panel Survey covering the period 1991-2002 to investigate single women's labour supply changes in response to three tax and benefit policy reforms that occurred in the 1990s. We find evidence of small labour supply effects for two of such reforms. A third reform in 1999 instead led to a significant increase in single mothers' hours of work. This increase was primarily driven by women who changed job, suggesting that labour supply adjustments within a job are harder than across jobs. The presence of hours inflexibility within jobs and labour supply adjustments through job mobility are strongly confirmed when we look at hours changes by stated labour supply preferences. Finally, we find little overall effect on wages.
Keywords: C23; H31; I38; J12; J13; J22; 330; Job mobility; Hours flexibility; Labour supply preferences; Hours-wage trade-off; Monopsony; Arbeitszeit; Arbeitszeitgestaltung; Arbeitsmobilität; Teilzeitarbeit; Weibliche Arbeitskräfte; Großbritannien